THE POSIBILITY IMPACTS OF FREE FLOW OF GOODS IN ASEAN ECONOMIC COMMUNITY ON INDONESIA ANTI DUMPING ACTIONS - Abdurrahman Alfaqiih (Fakultas Hukum Universitas Gadjah Mada, 2015)
One of the top aims of ASEAN Economic Community (AEC) establishment is to create trade that is free from any kind of barriers. Nonetheless, not every country could follow the wave of free trade without imposing protection assessment such anti-dumping measures. This paper tries to identify the possibility impacts of free flow of goods scheme on the use of antidumping in Indonesia. By imposing content analysis, this paper concludes that the possible effects tend to be increase or decrease the use of anti dumping actions; and the possibility of elimination of anti-dumping measures and replacement with competition policy. Salah satu tujuan utama dari pembentukan Masyarakat Ekonomi ASEAN (MEA) adalah menciptakan perdagangan yang bebas dari hambatan. Namun demikian, tidak semua negara dapat mengikuti gelombang perdagangan bebas tanpa menerapkan kebijakan perlindungan dalam negeri seperti ketentuan anti-dumping. Tulisan ini mencoba untuk mengidentifikasi kemungkinan efek dari peredaran barang yang bebas dalam (MEA) terhadap penggunaan kebijakan anti-dumping di Indonesia. Dengan menggunakan analisis isi, tulisan ini menyimpulkan bahwa kemungkinan efek tersebut dapat menjadikan penggunaan kebijakan anti-dumping di Indonesia meningkat atau menurun, dan juga kemungkinan penghilangan kebijakan antidumping serta menggantikannya dengan kebijakan persaingan usaha.